#TITLE_ALTERNATIVE# - AHMAD WIHARDI (NIM : 13104001); Pembimbing Utama Prof. Dr. Ir. Muljowidodo, PRIMA
Wing In Surface Effect (WiSE) is a low-flying aircraft near the surface. Fly with low altitude aircraft is intended to get additional lift from the surface effects and maximize the ratio of lift to drag (lift to drag ratio). Where surface effects can occur if the aircraft altitude is lower than the aircraft wing chord length. Final report on PARWISE Craft is about aspects of aerodynamics, propulsion system, takeoff analysis and manufacturing processes. To help the process of data processing and analysis, the authors use the help of software, among others: DesignFoil R6, Solidworks 2010, CFD Gambit 2.2.30, 6.2.16 Fluent CFD, Microsoft Office 2010 and Microsoft Excel 2010. Issues that will be studied and reviewed in this final report berkitan with simlasi CFD, propulsion testing and analysis PARWISE Craft takeoff. CFD simulations carried out to obtain aerodynamic data (Lift, Drag and Moment) from the model that has been made. Propulsion system testing to obtain data on engine performance and maximum thrust power generated. Takeoff analysis conducted to predict the propulsion power is used if able to fly the plane. At takeoff conditions of work so that the aerodynamic and hydrodynamic propulsion power required is greater. Therefore, Power Augmented Ram (PAR) applied technology in the model to assist during the takeoff. Where PAR technology can occur when air flow from the propulsion propeller spin directed downwards main wing leading edge, causing a large pressure difference between the lower and upper wing surfaces (the principle of hovercraft). The pressure difference resulted Lift-drag ratio increase it expected the plane can be lifted from the surface so that the hydrodynamic force that eventually can decrease aircraft capable of takeoff.